SPECTROFLUORIMETRIC DETERMINATION OF EOSIN CHEMILUMINESCENCE SYSTEM FOR THE ANALYSIS OF DABIGATRAN IN PHARMACEUTICAL FORMULATIONS - DHANAPAL Y; SRUDHIVINOD V; MOHAMAD WASEEM A (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objectives of this study were to develop a rapid, simple, and economical spectrofluorometric method for quantification of dabigatran from marketed formulation and its principle involved based on the protonated process of a binary mixture complex formation with eosin Y. Methods: A simple and precise spectrofluorometric technique was applied for the method development. It depends on measuring the quenching effect of the drug on the native fluorescence of eosin at excitation under the optimum reaction conditions. Results: The reaction linear calibration graph constructed between the fluorescence quenching valves flouresence intensity (ΔF) and the concentration ranges of 5–50 μg/ml. Spectrofluorometric analytical performance was validated by accuracy, precision, and specificity, and the results were satisfactory. Conclusion: This method was to develop a fast, simple, and economically applied successfully for the assay, and qualification of dabigatran tablet contains drug, also with different coformulated pharmaceutical formulations.